STRATEGI IKATAN MOTOR BESAR INDONESIA (IMBI) PENGURUS DAERAH (PENGDA) BALI DALAM MENINGKATKAN CITRA MOTOR BESAR MELALUI KEGIATAN CORPORATE SOCIAL RESPONSIBILITY (CSR) - dwi krisna; dewa rejana (Jurnal Ilmiah Dinamika Sosial, 2017)
ABSTRACTIn the corporate context, an activity known as the manifestation of corporate social responsibility. This includes how the commitment of a company or organization to contribute to the development of the environment in which it established. In addition to meeting moral ethics, the implementation of social responsibility also has an impact on improving the image of the organization. Image is not the most important thing, but it was included on the ultimate goal for an organization. Related to this, the image is considered important as it will be a determinant of how the social environment provides an assessment of the organization and its members. Nevertheless to non-profit organizations such as the Ikatan Motor Besar Indonesia (IMBI), whose image was tarnished several times due to the arrogance of irresponsible motorists, most of whom were not members of the organization. This study examines how the efforts done by the Ikatan Motor Besar Indonesia (IMBI), especially on the Bali regional authorities, in order to get closer to the community, enhance the positive image that already exists as an officially recognized organization for big bikes in Indonesia, as well as reducing the public's negative perception of the big bikers. This effort is done by Ikatan Motor Besar Indonesia (IMBI) Bali regional authorities through corporate social responsibility (CSR) activities. This research uses descriptive qualitative approach. With analysis using communication planning scheme initiated by Philip Lesly, the result of this research shows that the Ikatan Motor Besar Indonesia (IMBI) Bali regional authorities has been able to obtain the expected image, which is a better or more pleasant image than the existing image. The study also found that there are no significant obstacles to the Ikatan Motor Besar Indonesia (IMBI) Bali regional authorities in the implementation of corporate social responsibility (CSR) activities.Keywords: Strategy, Corporate Social Responsibility, Image, Big Bike